A New Control Method Based on Artificial Immune Adaptive Strategy - Peng, Yonggang; Luo, Xiaoping; Wei, Wei (Elektronika ir Elektrotechnika, 2013)
An Artificial Immune Adaptive Strategy combining immune adaptive control and immune genetic optimization is proposed based on the simulation of the immune mechanisms such as the antibodies’ bifunctional structure and the immune cells’ regulation principle. This strategy is capable of optimizing online parameters of the immune controller with fixed framework, better simulating the behavior of the biological immune system. The proposed artificial immune adaptive strategy is applied to the control of Continuous Stirred Tank Reactor and its performance is compared with that of Cerebellar Model Articulation Controller. The results validate the effectiveness of artificial immune adaptive strategy. DOI: http://dx.doi.org/10.5755/j01.eee.19.4.1246